Unmanned aerial vehicles in land surveying - Deryglazov, Danylo (Запоріжжя: НБ ТДАТУ, 2025)
Unmanned aerial vehicles (UAVs) or drones have now become an essential component of surveying as they can capture accurate and instant aerial photographs. Sophisticated drones possess high-resolution cameras and laser scanners that allow them to create three-dimensional models of landscapes, scan extensive areas and monitor buildings and structures. Among the main advantages of drone technology in geodesy is that they can reach remote, hard-to-reach areas, such as mountain or forest areas, where traditional measurement methods are limited. Drones avoid endangering employees as they never have to be in perilous or out-of-reach locations.
Keywords: unmanned aerial vehicles; drones; geodetic surveys